Employment and working conditions of low-skilled information-processing workers in less developed countries. - PEARSON, Ruth (1993)
Explores current and probable future trends in the employment of the lower-skilled workers in computing and information processing in developing countries. Draws on evidence from Brazil, Jamaica and Malaysia, to assess the expansion of data-processing employment both offshore and in public administration. Surveys employment conditions in the industry.